Analysis of Crisis Communication Management Study: Study at PT Semen Baturaja (Persero) - Sandi, Yoki Famila (Arkus, 2024)
Crisis communication management is the process of planning, implementing and evaluating communications carried out in the face of a crisis. Effective crisis communication management can help companies to: maintain the Company's reputation, minimize the impact of the crisis on the company, prevent the spread of incorrect information, and build public trust in the company. This research is qualitative research. This research was conducted online by utilizing various online communication features to obtain information from informants. The informants in this research were the management of PT Semen Baturaja (Persero) and supplier partners and consumers from PT Semen Baturaja (Persero). PT Semen Baturaja has a good commitment to handling the crisis. The company has demonstrated efforts to improve the transparency, speed and effectiveness of crisis communications. However, PT Semen Baturaja still has several opportunities to improve its crisis communication management. These companies can increase the effectiveness of crisis communications on social media by using simple language, images and videos, fast and responsive responses, and various social media features.